PENGARUH DEBT TO EQUITY RATIO (DER), UKURAN PERUSAHAAN(SIZE), NET PROFIT MARGIN (NPM) DAN RETURN ON ASSETS (ROA)TERHADAP PERATAAN LABA (IS) - M Alim; Rasmini Rasmini (Universitas Muhammadiyah Tangerang, 2019)
Income smoothing is a phenomenon used by management with the aim of reducing variability in earnings over a certain period or in a period, which leads to the expected level of reported earnings. Efforts to reduce the fluctuation of earnings is a form of profit manipulation so that the amount of profit in a period is not too different from the amount of profit in the previous period. Therefore, income smoothing involves the use of certain techniques to reduce or increase the amount of profit of a period with the amount of profit of the previous period. However, this effort is not to make a profit of a period equal to the amount of the profit of the previous period, because in reducing the fluctuation of profit also considered the normal growth rate expected in that period.